Speaking in a second language - Alonso Alonso, Rosa (AILA applied linguistics series, 2018)
For millions of individuals all over the world, speaking in a second language is a daily activity. It is therefore important that research in applied linguistics should contribute empirically to the study of second language spoken interaction. The aim of this volume is to make such a contribution by providing research-based insights into current approaches to the teaching and learning of this skill. Two key dimensions define the papers included here-their novelty and scope. First, the book provides a novel approach to the study of speaking in a second language by combining recent findings in usage-based linguistics with current issues in teaching. Second, the chapters cover a range of theoretical perspectives, including sociolinguistic and interactional competence, gestures, dynamic systems theory and code-switching. The volume offers a contemporary analysis of research in second language speaking that will be of interest to researchers, graduate students, teachers and other professionals working in the fields of communication and applied linguistics.